Studies on variability in cumin (Cuminum cyminum L.) on normal and saline soil - BHARGAVA, S C MAHALA, L S DHAYAL, S C (Journal of Spices and Aromatic Crops, 1999)
Studies on variability in nine genotypes of cumin (Cuminum cyminum) (VC-217, VC-198, VC-216, VC-209, Local, VC-218, VC-89, RS-1 & VC-208) conducted at Jobner, India, indicated higher estimates of genotypic coefficient of variance, phenotypic coefficient of variance, heritability and genetic advance for plant height, number of umbels per plant, number of grains per umbel, test weight;grain yield per 10 plants, on normal soil and number of grains per umbel and test weight on saline soil, suggesting the probable role of additive gene effects on character expression.